Proteasomal Degradation Machinery: Favorite Target of HIV-1 Proteins - Lata, Sneh; Mishra, Ritu; Banerjea, Akhil C. (Frontiers in Microbiology, 2018)
Proteasomal degradation pathways play a central role in regulating a variety of cellular functions of proteins by controlling not only their turnover but also physiological behaviour of the cell. This makes it an attractive target for the pathogens especially viruses which rely on the host cellular machinery for their propagation and pathogenesis. Viruses have evolutionarily developed various strategies to manipulate the host proteasomal machinery thereby creating cellular environment favourable for their own survival and replication. Human Immunodeficiency Virus – 1 (HIV-1) is one of the most dreadful viruses which has rapidly spread throughout the world and caused high mortality due to its high evolution rate. Here, we review the various mechanisms adopted by HIV-1 to exploit the cellular proteasomal machinery in order to escape the host restriction factors and components of host immune system in order to support its own multiplication and establish a successful infection.